Analisis Determinan Indeks Harga Saham Kelompok Jakarta Islamic Index pada Masa Sebelum dan Saat Pandemi Covid-19 - Rahmatulloh, Cikal Muzammil; Kristianingsih, Kristianingsih; Pakpahan, Rosma; Mayasari, Ine (Journal of Applied Islamic Economics and Finance, 2023)
The large value of the stock price is thought to be caused by the company's internal factors, namely EPS, PER, and PBV on the Share Price Index in the JII Group Before and During the COVID-19 Pandemic. The research data comes from the company's financial reports that are consistent and registered with the JII group for 2018-2021 using purposive sampling. Data analysis is descriptive quantitative using the panel data regression method, classic assumption test, t test and F test using the Eviews Version 12 tool. From the research that has been conducted, the results obtained are that EPS has a positive effect before COVID-19 (2018-2019) and had a negative effect during COVID-19 (2020-2021), PER had no effect before and during COVID-19 (2018-2021), and PBV had no effect before COVID-19 (2018-2019) and had an effect during COVID -19 (2020-2021). And simultaneously, EPS, PER and PBV affect the Stock Price Index.